النظام القانوني للمجلس الشعبي الوطني - زين, صلاح الدين; شارف, البشير; عوادي, زين الدين (جامعة الوادي university el-oued, 2022)
يعتبر المجلس الشعبي الوطني من أبرز المؤسسات الدستورية التي أقرها المؤسس الدستوري الجزائري، فهو يشكل السلطة التشريعية إلى جانب مجلس الأمة. فقد شهدت الغرفة الأولى للبرلمان تطورات متسلسلة، ابتداءً من صدور أول دستور للجمهورية الجزائرية سنة 1963، إلى غاية التعديل الدستوري الأخير لسنة 2020. وقد اقتصر هذا البحث على إظهار وإبراز أهمية ومكانة المجلس الشعبي الوطني على المستوى المؤسساتي والوظيفي، باعتباره هيئة دستورية منتخبة معبّرة عن الإرادة الشعبية، وهو القائم على وضع القاعدة القانونية إلى جانب مجلس الأمة، بالإضافة إلى ذلك فهو يراقب ويتابع نشاط الحكومة. لكن ومن خلال دراستنا هذه تبيّن لنا أن هذه الوظائف التي يتمتع بها المجلس الشعبي الوطني، المتمثلة في الوظيفة التشريعية والوظيفة الرقابية معطّلة وغير مفعلة، وذلك بسبب هيمنة السلطة التنفيذية عليها.The People's National Assembly (PNA) is considered as the main consistinal embassies which approved by the algerian constitutional council that represents the legislature authority the same as the Council of the Nation. The Lower House of the Algerian Parliament witnessed a series of developments starting with the release of the first constitution of the Republic of Algeria in 1963 till the recent constitutional amendment of the year 2020. This research shows and highlights the importance and the place of the PNA in the institutional and the career level as it is a constitutional elected body that represents the popular will who puts the law basics with the council of nation. In addition to that, it watches and follows the government activities. Nevertheless, through our studies, it appear that the authorities that the PNA have is represented by the legislative function, the supervisory function is deactivated due to the domination of The executive branch on it.
مذكرة ماستر